Pengaruh Suhu Lingkungan Terhadap Aktivitas Enzim Katalase Pada Hati Ayam - Adisti (Jurnal Ilmu Pendidikan Biologi dan IPA, 2025)
The catalase enzyme is a vital antioxidant enzyme whose activity is influenced by environmental factors such as temperature. This research aimed to investigate the effect of temperature variation on the activity of the catalase enzyme isolated from chicken liver (Gallus gallus domesticus). A laboratory experimental method was used by measuring the catalase activity in a crude extract of chicken liver. The enzyme extract was incubated at five different temperatures: 5°C, 27°C, 37°C, 47°C, and 57°C. Enzyme activity was determined spectrophotometrically by measuring the decomposition rate of the hydrogen peroxide (H2O2) substrate. The results showed that temperature has a significant influence. Enzyme activity was observed to be low at 5°C, then increased with rising temperature, reaching its peak (optimal) activity at 37°C. At higher temperatures (47°C and 57°C), the enzyme's activity decreased sharply. The decrease in activity at low temperatures was caused by reversible inactivation, whereas at high temperatures it was caused by irreversible thermal denaturation. The optimal temperature of 37°C indicates the enzyme's adaptation to function efficiently at the normal physiological temperature of chickens. In conclusion, temperature is a critical factor that controls the catalytic function of the catalase enzyme.